The effects of chloroquine phosphate on the serum level of proinflammatory interleukins in patients with knee osteoarthritis. - Jawad, Haider M.; Salman, Sami; Kathum, Ali (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Osteoarthritis is the most common joint disorder. Treatment is usually limited to short term symptom relived and is by no means satisfactory.